Supportive care needs and health-related quality of life in cancer patients receiving palliative care - Schnabel, Astrid; Lordick, Florian; Oberth, Paula; Neuschulz, Markus; Lehmann-Laue, Antje; Mehnert-Theuerkauf, Anja; Hinz, Andreas (Frontiers in Psychology, 2023)
Objective: Cancer patients receiving palliative care experience a variety of impairments in their quality of life (QoL), and have corresponding supportive care needs (SCNs). The aim of this study was to analyze the relationship between SCNs, satisfaction with QoL dimensions, and the perceived importance of these dimensions. Method: A sample of 152 cancer patients receiving palliative care were included in this cross-sectional study. Eight dimensions of QoL were defined and assessed concerning SCNs, satisfaction, and subjective importance using a new assessment instrument with five-point scales (range 1-5) for each dimension. Results: Among the eight specific domains examined, the greatest SCNs were observed for absence of pain (M = 3.18; SD = 1.29). The patients were least satisfied with their physical functioning (M = 2.60; SD = 0.84), and the dimension social relationships (M = 4.14; SD = 0.72) received the highest perceived importance ratings. The eight dimensions’ SCNs scores were significantly correlated with each other (r between 0.29 and 0.79); the lowest correlations were found for social relationships. The correlations between the satisfaction scores and the SCNs differed from dimension to dimension, with coefficients between -0.32 (absence of pain) and -0.57 (sleep quality). Conclusion: The results show that detriments in QoL do not automatically indicate high levels of SCNs in those dimensions. Health care providers should consider both factors, QoL (as measured with QoL questionnaires) and subjectively expressed SCNs, to optimize their patients’ care regimens.